Spiritual Leadership and Green Creativity: A Multilevel Analysis (Journal of Social Sciences Review, 2023)
The current research examines the influence of spiritual leadership on green creativity via the mediating mechanism of green knowledge-sharing by supporting social learning theory. Leaders with spiritual traits can create green knowledge sharing that leads to green employee creativity. Rationally, this research follows the mechanism of post-positivism. Therefore a quantitative methodology is applied. Time-delayed survey administration and deductive approach are applied for theory development. Multilevel data is collected from 405 employees working in Pakistani universities and hospitals. Multilevel pathway analysis is implemented by using Mplus. Our research established a statistically positive influence of spiritual leadership on green knowledge-sharing, which increases green creativity. Our study provides various practical and managerial consequences where organizations can intentionally emphasize and concentrate on employees' green creativity to save the environment through employees' implementation of green ideas.
Keywords: Spiritual Leadership; Green Knowledge Sharing; Green Creativity; Multilevel; Environmental Degradation